(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article examines the indirect involvement of the Mexican government, headed by Alvaro Obregon, in the fifth Conference of American States in Santiago, Chile in 1923. We review the positions the Mexican government took and the impact it had on the outcome of that event. During the conference the inter-American structure that the U.S. built since the late nineteenth century through its Pan American integration project was questioned. The criticism made by a group of Latin American diplomats toward that structure was inspired by the exclusion that the directors of the Pan American Union made of the Mexican government . The conference was therefore a diplomatic battle fiel against U.S. intervention in defence of the sovereignty of latin American countries.